The Effects Of Time Constraints And Proficiency On Esl Essay Writing Performance - Chan, Weng Fatt (Universiti Sains Malaysia, 2007)
This study investigated the effects of time and proficiency on ESL writing performance. The subjects of the study were two groups of undergraduates, namely proficient and less proficient speakers of English. To test the effects of time and English proficiency on their writing performance, the subjects each wrote a 45-minute essay and a 30-minute essay. These essays and the prewriting drafts form the basic corpus of the study. To complement the data from the essays, the study also employed structured questionnaires that tapped relevant information from subjects concerning their writing with regard to their English proficiency and time constraints. The study employed a two by two factorial design in its methodology to determine the interaction effects of time and proficiency, and the main effects on essay scores, component scores and prewriting drafts. The factorial design was used because it was appropriate and effective in multi-factored studies such as this which involved the interaction of time and proficiency with essay writing and essay components. The analyses reveal that the total essay scores and three of the five component scores of essays written in 45 minutes were significantly better than those written in 30 minutes. The analyses of the questionnaire responses suggest that the subjects viewed the adequacy of time due to the extra 15 minutes, as the reason for the increase of essay scores and component scores in the 45 minute essays.